A Better Solution Towards Microservices Communication In Web Application: A Survey (International Journal of Innovative Research in Computer Science & Technology, 2019)
Most of the software applications are configured as  client-server fashion in the network in order to enable  communication among them. But sometimes these applications  must be able to communicate or exchange data between clients  and server that are not always up and active. One of the  solutions to such issues is to enable applications to store  information and communicate asynchronously with other. Thus  in this regard Message Oriented Middleware (MOM) which  support massage queue based communications are becoming  more and more popular today. It is the task of developer to  choose the suitable broker for his applications. Thus one has to  compare different MOM based brokers to select suitable and  efficient ones. This paper mainly compares two brokers RabbitMQ and RESTful API. By conducting survey on different  experimental results it can be concluded, that when large number  of users are involved in network communication, RabbitMQ is  more stable and suitable to use.
Keywords: RabbitMQ; RESTful API; Message Oriented Middleware (MOM)